Textual Organization of Request Letters in Spanish and English and of Request Memoranda in Spanish: an Exploratory Study - Martínez Contreras, María Stella; Moreno Castrillón, Francisco (Íkala, Revista de Lenguaje y Cultura, 2004)
This paper describes a genre-based analysis of a group of request letters in Spanish and English and of request memoranda in Spanish, all produced by native speakers of Spanish1. The framework of analysis adopted is based on the concept of genre proposed by Swales (1990) and Bathia (1993). The generic description of these letters and memoranda shows which moves appear to be more conventionalized. The relationship between contextual factors and the choice of moves is explored. This paper concludes that this type of analysis can provide useful insights into the design of teaching materials for business communications in Spanish and English. Recieived: 31-05-04 / Accepted: 13-09-04 How to reference this article: Martínez Contreras, M. S. & Moreno Castrillón, F. (2004). Textual Organization of Request Letters in Spanish and English and of Request Memoranda in Spanish: an Exploratory Study. Íkala. 9 (1), pp. 83 – 102